Beitrag zur Faunistik der Rüsselkäfer Bulgariens (Coleoptera - Curculionidae). - Behne, Lutz (Contributions to Entomology = Beiträge zur Entomologie, 1989)
The present paper evaluates 597 species collected in Bulgaria, of which 213 species are listed here. A total of 48 species could be established as new in Bulgaria. Existing taxonomical problems of some species and genera are pointed out.